The Diversity And Abundance Of Free-living Marine Nematode In Northern Peninsular Malaysia - Abdul Samad, Nur Shakila (2019)
Limited studies were conducted in Malaysia especially in Peninsular Malaysia on marine nematodes as little attention given to marine nematodes than plant and animal parasitic nematode. But their small size, high abundance and rapid turnover rate is useful tool in providing information on ecosystem functioning. Hence, the aim of this study was to determine diversity and abundance of free-living marine nematode and its feeding groups among locations in northern Peninsular Malaysia and to identify whether any changes in nematode community are related to particular environmental variables. The sample collections were carried out twice in each location during low tide along the intertidal zone in five locations which are in Penang: Teluk Aling, Pasir Pandak, Pulau Gazumbo; Langkawi Island: Tanjung Rhu and Perak: Kuala Sepetang as these locations had different human activities and anthropogenic disturbances. There were 21 environmental parameters studied in this study which were sediment and pore water temperature, dissolved oxygen, salinity, pH, sediment composition, chlorophyll a biomass, pore water nutrients (NCh", NOs', NH3, PCL3') and heavy metal elements (Fe, Zn, Ni, Pb, Cr, Cd, Cu). A total of 52 genera belonged to 25 families were identified in this study.